Topological redundancy and 'small‐world' patterns in a food web in a subtropical ecosystem of Brazil. (16th December 2016) - Bornatowski, Hugo; Barreto, Rodrigo; Navia, Andrés F.; de Amorim, Alberto Ferreira
Abstract: According to graph theory, the frequency distribution of trophic interactions within a food web has deep structural implications, as it can highlight the presence of patterns associated with the web and indicate whether the properties of the web are independent of its size. A hypothesis is that 'small‐world' food webs are sensitive to the loss of species with the highest values. Therefore, the present work aimed to evaluate the degree to which a subtropical food web in Southern Brazil displays small‐world patterns and their resistance. As part of the assessment, we evaluated the topological redundancy values of species in the food web and then we simulated the exclusion of these species (such as sharks and sea birds), and also the exclusion of high centrality species (such as squids Loligo sp., portunid swimming crabs and the cutlassfish Trichiurus lepturus ). The food web showed a 'broad‐scale' distribution of connections by node, and a small‐world pattern. As expected, a simplification of the network was observed after elimination of some species with high centrality. However, the food web was resistant to the loss of species with low topological redundancy, probably because these species occupy a high trophic level and do not participate in lots of routes within the food web. We highlight however, the importance of the application of multiple analyses to evaluate the importance of components in food webs, and fisheries management plans should consider both species of high centrality values and species with low topological redundancy.